2018
DOI: 10.1016/j.conbuildmat.2018.07.169
|View full text |Cite
|
Sign up to set email alerts
|

Recycled glass fiber reinforced polymer composites incorporated in mortar for improved mechanical performance

Abstract: Form approved OMB No. Public reporting for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestion for reducing this burden to Washington Headquarters Services, Directorate for Information Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…For plastics and polymers, which are two of the main industrial byproducts and home waste materials [ 2 ], various processes are being conducted to reuse and recycle them, such as mechanical recycling (secondary polymers are obtained through mechanical processes), chemical recycling (monomers are recovered to be employed as new virgin polymers or are transformed in other useful materials), and energy recovery (energy is obtained from the combustion of post-consumer plastics) [ 3 , 4 , 5 , 6 , 7 ]. Additionally, the introduction as fillers in other materials is becoming a possible solution for plastic and polymeric waste materials, especially in construction materials, with examples of reuse in various structural materials, such as concrete [ 8 , 9 , 10 , 11 , 12 , 13 ], mortars [ 14 , 15 , 16 , 17 , 18 ], bituminous materials for pavements [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], and gypsum [ 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…For plastics and polymers, which are two of the main industrial byproducts and home waste materials [ 2 ], various processes are being conducted to reuse and recycle them, such as mechanical recycling (secondary polymers are obtained through mechanical processes), chemical recycling (monomers are recovered to be employed as new virgin polymers or are transformed in other useful materials), and energy recovery (energy is obtained from the combustion of post-consumer plastics) [ 3 , 4 , 5 , 6 , 7 ]. Additionally, the introduction as fillers in other materials is becoming a possible solution for plastic and polymeric waste materials, especially in construction materials, with examples of reuse in various structural materials, such as concrete [ 8 , 9 , 10 , 11 , 12 , 13 ], mortars [ 14 , 15 , 16 , 17 , 18 ], bituminous materials for pavements [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], and gypsum [ 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The test results showed that 3 wt % aggregates replacement with GFRP attained maximum compressive and flexural strength. Adding recycled GFRP into concrete improves the impact strength of concrete, but it will reduce the slump flow [24][25][26]. The chopped recycled CFRP improves the compressive, flexural, and impact strengths of concrete [27][28][29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scrap composites are cut using slow cutting or crushing mills to aid in the removal of metal inserts and transportation to a size of 50-100 mm, while in the second stage high-speed mills or hammer mills are used to reduce the composite size to 10 -50 mm [17,18]. Ultimately, cyclones and sieves are used to grade recyclate volumes into various scale fractions [19]: fine powders [20], coarse [21] or fibrous [22]. There are many reports on possible uses of the obtained recyclates.…”
Section: Mechanical Recyclingmentioning
confidence: 99%